THE ROLE OF CHATGPT IN IMPROVING LEARNING EFFECTIVENESS AND STUDENT SATISFACTION: FINDINGS FROM THE INFORMATICS EXAM SURVEY - Efendi, Dedi; Putri, Hesi Eka; Putri, Hesi Eka; Wati, Salmi; Albert, Albert (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Amazing technological developments like ChatGPT have delivered tremendous benefits while posing complex challenges in education. Not surprisingly, a heated debate among academics erupted around the impact and benefits that ChatGPT presents in the context of learning. This study aims to understand more deeply students' perceptions of the use of ChatGPT in education, an aspect that is so important considering that students are one of the main actors involved in these interactions. Adopting a mix method approach that combines quantitative and qualitative analysis, this study was conducted on 30 students at MAN 5 Agam. Through the use of questionnaires and interviews, research data were carefully collected. The findings show that students positively welcome the ease of utilizing ChatGPT, the enrichment of knowledge offered, and satisfaction with the fast and accurate responses provided by ChatGPT. Time efficiency and increased learning activity were also noted as significant benefits of using ChatGPT. However, there are serious concerns about ChatGPT's inability to increase learning motivation. Concerns about unfair assessment processes and the risk of plagiarism that has the potential to damage critical thinking skills are also important points that arise from this study. The results of this study encourage suggestions for future research related to the integration of ChatGPT in education in order to strengthen learning motivation in students. Thus, the use of technology can be optimized as an effective tool in enriching the learning process in the digital era.